Accurate empirical rovibrational energies and transitions of H216O. Issue 7 (11th January 2019) - Tóbiás, Roland; Furtenbacher, Tibor; Tennyson, Jonathan; Császár, Attila G.
Abstract : Several significant improvements are proposed to the computational molecular spectroscopy protocol MARVEL (Measured Active Rotational–Vibrational Energy Levels), facilitating the inversion of a large set of measured rovibrational transitions to energy levels. Abstract : Several significant improvements are proposed to the computational molecular spectroscopy protocol MARVEL (Measured Active Rotational–Vibrational Energy Levels) facilitating the inversion of a large set of measured rovibrational transitions to energy levels. The most important algorithmic changes include the use of groups of transitions, blocked by their estimated experimental (source segment) uncertainties, an inversion and weighted least-squares refinement procedure based on sequential addition of blocks of decreasing accuracy, the introduction of spectroscopic cycles into the refinement process, automated recalibration, synchronization of the combination difference relations to reduce residual uncertainties in the resulting dataset of empirical (MARVEL) energy levels, and improved classification of the lines and energy levels based on their accuracy and dependability. The resulting protocol, through handling a large number of measurements of similar accuracy, retains, or even improves upon, the best reported uncertainties of the spectroscopic transitions employed. To show its advantages, the extended MARVEL protocol is applied for the analysis of the complete set of highly accurate H2 16 O transition measurements. As a result, almost 300 highly accurate energy levels of H2 16 O are reported in the energy range of 0–6000 cm −1 . Out of the 15 vibrational bands involved in accurately measured rovibrational transitions, the following three have definitely highly accurate empirical rovibrational energies of 8–10 digits of accuracy: ( v 1 v 2 v 3 ) = (0 0 0), (0 1 0), and (0 2 0), where v 1, v 2, and v 3 stand for the symmetric stretch, bend, and antisymmetric stretch vibrational quantum numbers. The dataset of experimental rovibrational transitions and empirical rovibrational energy levels assembled during this study, both with improved uncertainties, is considerably larger and more accurate than the best previous datasets.